Cathodic protection by distributed sacrificial anodes - Performance at Elevated Temperature and in Mud - Ryen, A.; Johnsen, R.; Iannuzzi, Mariano; Årtun, L. (2018)
© 2018 by NACE International. Thermal Spray Aluminum (TSA) can be used to reduce anode demand or to extend anode life on projects with long design lives (i.e., 40 to 50 years). However, for subsea structures, TSA has not been used to replace the functionality of sacrificial anodes. In conventional CP design, TSA should not degrade while it remains connected to the CP system, draining current from sacrificial anodes, which ensure adequate cathodic protection. During the CORROSION 2017 conference, a new concept named CP by distributed sacrificial anodes (DSA) was presented.1 The main principle was to convert the cathode area to anode area by distributing anode mass over the surface of the equipment to be protected. CP by DSA is achieved by the deposition of a single-layer metallic coating. In this work, DSA was applied by thermal spray (TS). DSA reduces the total exposed cathode area to small defects and imparts active cathodic protection. In previous work, the outcome of exposure testing in flowing natural seawater at 10°C was discussed. In this paper, exposure in seawater at 50°C and 80°C and in mud, are discussed. Freely exposed samples thermally sprayed with DSA and conventional TSA as well as galvanic couplings between DSA and both TSA and carbon steel were investigated.